Community Based Cross-Sectional Study to Assess the Health Problems and Quality of Life Among Migrant Construction Workers in Chennai - Veerabathiran Manikandan; Ruchita Jain; Ramaiha Dhanasekaran Sandhiya; Premnath Arulmozhi; Arun Murugan; Sathishkumar K; Gunasekaran Aravind; Vijaiyalakshmi Praveen (National Scientific Medical Center, 2024)
BACKGROUND Migrants tend to have an increased risk of physical and mental ill health, but less access to health care services. Hence this study was conducted with the following objectives: to describe the health problems among Migrant construction workers in Chennai, to determine the quality of life of Migrant construction workers in Chennai and to assess the Health seeking behaviour of Migrant construction workers in Chennai METHODS This was a community based Cross-sectional study conducted in construction sites in Chennai. Interstate migrant construction laborers including men and women aged more than 18 years who are working in the construction sites for more than 1 year were included in the study. The study was conducted from March to April 2023. Sample size was calculated to be 400 and convenient sampling was used. Structured and pretested Validated Questionnaire was used for data collection. RESULT: The study showed that 13% had respiratory disease, 5.1% had acute febrile illness and 5.1 % had gastrointestinal disease. About 13% of the respondents went to nearby medical shop when they have any medical problems. About 41% of the repondents had poor QOL and quality of life was very poor in 5% of the respondents.